A critical discourse analysis physical characteristics of traditional Terengganu architecture as a tourist attraction on the east coast of Peninsular Malaysia: a case study of Terrapuri Heritage Village in Terengganu - Ismail, Sumarni; Ismail, Nor'atiah; Siow, May Ling; Zainal Abidin, Izzati; Mohd Hamdan, Nur Aina Abidah; Sazli, Siti Sara (Universiti Malaya, 2024)
Traditional Terengganu architecture, including the Rumah Bujang Berselasar (bachelor house with an unroofed platform) and Rumah Tiang Dua Belas (twelve-pillared house), is the earliest and most prevalent type of housing in the northeastern region of Peninsular Malaysia, specifically in Terengganu. Site observation was conducted in Terrapuri Heritage Village in Setiu, Terengganu. These Malay houses are considered a crucial part of the region’s architectural history, reflecting numerous changes in their architectural elements and their continuity with the past and present built environment. Beyond being mere structures for shelter, the physical characteristics of these houses embody traditional values, beliefs, and ways of life. Rooted in the rich cultural heritage of the Malay community, they have been shaped over centuries by history, geography, and social interactions. Hence, studying the physical features of traditional Terengganu architecture requires an interdisciplinary approach that encompasses not only technical and functional aspects but also cultural and symbolic significance. This necessitates integrating architectural and construction principles with social, cultural, and historical perspectives. The objective of this study is to identify the structural and non-structural elements of traditional Terengganu houses, specifically Rumah Bujang Berselasar and Rumah Tiang Dua Belas. These distinctive features reflect the local context and cultural influences, contributing to the creation of a coastal resort identity. Thus, it is imperative to continue efforts to preserve and promote traditional Malay architecture, including Rumah Bujang Berselasar (bachelor house with unroofed platform) and Rumah Tiang Dua Belas (twelve-pillared house), to ensure the sustainability and preservation of cultural heritage for future generations to come.